(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The north-westerly part of the present-day state of Telangana, which was then Andhra Pradesh, has a distinct culture from the rest of the Telugu-speaking areas. Authentic traditions, tales, and rituals grounded in myth and symbolism abound during this state’s festivals. There are two particularly noteworthy features of the Telangana festivities. The first is the remarkable reverence and participation of female deities; the second is the secularism and inclusion of the festivities, which enthusiastically draw individuals of all faiths and all classes. Telangana’s cultural essence is an ebbing and flowing river of tradition and modernity. Its language, literature, arts, dances, crafts, and festivals signify a region where history and contemporary life coexist harmoniously. The cultural tapestry of Telangana extends beyond mere rituals and practices—it is deeply embedded in the lives of its people, creating a sense of identity and continuity. Through their exuberant celebrations and meticulous preservation of traditions, the people of Telangana continue to honor their past while shaping their future, illustrating a vibrant and indomitable cultural spirit. The study aims to evaluate the influence of Telangana’s culture and festivals on contemporary society. And finally, it explains the importance of these celebrations in society.